2018
DOI: 10.1186/s40623-018-0934-1
|View full text |Cite
|
Sign up to set email alerts
|

Imaging high-latitude plasma density irregularities resulting from particle precipitation: spaceborne L-band SAR and EISCAT observations

Abstract: High-latitude, small-scale plasma density irregularities are observed by the Advanced Land Observation Satellite 2, Phase Array type L-band Synthetic Aperture Radar-2 and the European Incoherent Scatter radar in Tromsø, Norway. Under high levels of ionization of up to approximately 300 km in height triggered by nighttime particle precipitation, high-resolution SAR images detect horizontal distributions of azimuth shifts resulting from the spatial gradients of electron density. The irregular electron density is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…It has been observed that the shielding does not get sufficient time to develop during the fastvarying IMF Bz conditions, the effect of convection electric field in the ionosphere can last for several hours due to multiple magnetic reconnections at dayside magnetopause that gives rise to multiple short-lived penetrations (Maruyama et al 2007;Wei et al 2008;Huang 2019). The periodic changes in TEC over high latitude are expected due to the particle precipitation during geomagnetically disturbed conditions (Sato et al 2018;Chernyshov et al 2020). Recently, Birch and Hargreaves (2020) reported that the quasi-periodic oscillations of 25-27 min in the F-region electron content at high latitude, the magnetic field at geosynchronous orbit are caused by the solar wind pressure and IMF.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the shielding does not get sufficient time to develop during the fastvarying IMF Bz conditions, the effect of convection electric field in the ionosphere can last for several hours due to multiple magnetic reconnections at dayside magnetopause that gives rise to multiple short-lived penetrations (Maruyama et al 2007;Wei et al 2008;Huang 2019). The periodic changes in TEC over high latitude are expected due to the particle precipitation during geomagnetically disturbed conditions (Sato et al 2018;Chernyshov et al 2020). Recently, Birch and Hargreaves (2020) reported that the quasi-periodic oscillations of 25-27 min in the F-region electron content at high latitude, the magnetic field at geosynchronous orbit are caused by the solar wind pressure and IMF.…”
Section: Discussionmentioning
confidence: 99%
“…For estimating h iono properly, we assumed the azimuth offset can include not only ionospheric azimuth offset but also the uniform bias. Furthermore, we considered the obtained solutions as invalid if h iono was within the possible range (250-450 km), considering that the ionospheric altitude is fixed to be a constant value within 350-450 km in most conventional ionospheric models for Global Navigation Satellite System (GNSS) positioning [28], and that estimation approaches of the ionospheric altitude based on azimuth subband shifts [29] and Faraday rotation of microwave signals [16] were proposed in recent years, estimating the ionospheric altitude at 250-280 km.…”
Section: Methodsmentioning
confidence: 99%
“…By now it is known that the reduction of the azimuth bandwidth enhances the contrast of the stripe pattern at the cost of losing azimuth resolution (Kim et al., 2017). In sub‐band images, it is able to capture ionospheric propagation effects due to density irregularities in the SAR signal (Kim et al., 2017; Sato et al., 2018). Figure 1c shows the sub‐band power image corresponding to 1/16th of the total bandwidth.…”
Section: Observationsmentioning
confidence: 99%